2021
DOI: 10.1016/j.asmr.2021.01.012
|View full text |Cite
|
Sign up to set email alerts
|

Patient Height may Predict the Length of the Anterior Cruciate Ligament: A Magnetic Resonance Imaging Study

Abstract: The purpose of this study was to measure the length and width of anterior cruciate ligament (ACL) tibial footprint using magnetic resonance imaging (MRI) and to evaluate correlation between patients' weight and height with the tibial footprint size. Methods: In total, 207 eligible patients underwent MRI scanning from June 2018 to June 2020. One hundred seventeen knees from patients aged 18 to 40 years old with intact ACL were included in this study. Data of weight, height, body mass index (BMI) from physical e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…3,4 Studies have shown differences in knee measurements between races and ethnicities. 5,6 However, until today, there has been no consensus of the normal patellofemoral morphology parameter measurements. It is often difficult to diagnose patellofemoral malalignment during clinical examination without obvious clinical symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 Studies have shown differences in knee measurements between races and ethnicities. 5,6 However, until today, there has been no consensus of the normal patellofemoral morphology parameter measurements. It is often difficult to diagnose patellofemoral malalignment during clinical examination without obvious clinical symptoms.…”
Section: Introductionmentioning
confidence: 99%